2018
DOI: 10.1136/jramc-2017-000821
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of caregiver burden in spouses and partners providing informal care to wounded, injured or sick (WIS) military personnel

Abstract: Caring for an injured or ill military spouse or partner is a difficult task, compounded by the complexity of dealing with potentially both their physical and mental health problems. However, research has also identified some positive aspects of caring that can strengthen intimate relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
(28 reference statements)
1
12
0
Order By: Relevance
“…considerable public health implications of increased risk Research into the mental health and well-being of for Veterans' family members. [9][10][11] However, research fo-intimate partners of serving and ex-serving military cused on ex-service members' intimate partners is far less personnel has concentrated on their higher levels of sec prevalent than research examining ex-service personnel, ondary traumatization/PTSD, 5,7,20 caregiver burden, [21][22][23][24] while research examining military-connected children and adverse mental health outcomes, 6,[25][26][27] including is often in a developmental context 10,12 or focused on alcohol/substance misuse. [28][29] These studies have shown childhood/adolescence, [13][14] leaving aside psychological a spectrum of effects and effect intensity as a result of outcomes in now-adult children.…”
Section: Introductionmentioning
confidence: 99%
“…considerable public health implications of increased risk Research into the mental health and well-being of for Veterans' family members. [9][10][11] However, research fo-intimate partners of serving and ex-serving military cused on ex-service members' intimate partners is far less personnel has concentrated on their higher levels of sec prevalent than research examining ex-service personnel, ondary traumatization/PTSD, 5,7,20 caregiver burden, [21][22][23][24] while research examining military-connected children and adverse mental health outcomes, 6,[25][26][27] including is often in a developmental context 10,12 or focused on alcohol/substance misuse. [28][29] These studies have shown childhood/adolescence, [13][14] leaving aside psychological a spectrum of effects and effect intensity as a result of outcomes in now-adult children.…”
Section: Introductionmentioning
confidence: 99%
“…For example, compared to spouses of healthy veterans, spouses of veterans with TBI or PTSD endorse higher levels of psychiatric symptoms including depression and anxiety (Arzi et al, 2000), as well as elevated somatic symptoms, such as fatigue, sleep disturbances, and headaches (Saban et al, 2016). Providing informal care to ill or injured service members has also been shown to negatively impact the mental health and well‐being of military spouses and intimate partners (Skomorovsky et al, 2017; Thandi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Military family caregivers (MFCGs) are the family and friends who provide unpaid care for injured service members and veterans (i.e., military care recipients, MCRs) that often take place at home (Thandi, Harden, Cole, Greenberg, & Fear, ). Advances in combat medicine have allowed more service members to survive injuries on the battlefield and return home (Kellermann & Elster, ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, based upon findings from national civilian caregiving samples, the cost‐savings are largely absorbed by the health problems that caregivers experience (National Alliance for Caregiving, ; Navaie‐Waliser et al, ). Although caregiving has been associated with positive effects on the caregiver, such as providing a sense of purpose and pride, research has also found caregiving to be associated with poorer well‐being (e.g., high depression, anxiety, and somatic symptoms) and reduced quality of life (QOL) in both civilian caregivers and MFCGs (Baker, Barker, Sampson, & Martin, ; Blue Star Families, ; Griffin et al, ; Tanielian et al, ; Thandi et al, ). Overall, MFCGs experience burdens that have significant public health implications.…”
Section: Introductionmentioning
confidence: 99%